READING ‘PRESIDENT’ POEM BY REMY SYLADO'S WITH POSMODERN PARODY - Nur Alifah Septiani; Lismalinda Lismalinda (JETLi: Journal of English Teaching and Linguistics, 2020)
The words in literary works give a double meaning that leads the reader to the thought that divides between it as a real event or the author's imagination. In this case Remy Sylado indirectly through his poem describes the imperfections of the president's figures that focus in this poem. In the postmodern parody no one gives a complete meaning. The discourse presented in the text ‘president’ is a dual code discourse related to the president of Indonesia in the past era which was presented at the present time. The presence was carried out with tickling parodies that tried to criticize a leader. It shows that in the text ‘President’ explained that there is nothing that can be interpreted as a whole and absolute meaning.